Investigation via morphological analysis of aluminium foams produced by replication casting (Fracture and Structural Integrity, 2013)
Foams and porous materials with cellular structure have many interesting combinations of physical and mechanical properties coupled with low specific weight. By means of replication casting it is possible to manufacture foams from molten metal without direct foaming. A soluble salt is used as space holder, which isremoved by leaching in water. This can be done successfully if the content of space holding fillers is so high thatall the granules are interconnected. One of the main advantages of using the replication casting is a close control of pore sizes which is given by the distribution of particle sizes of the filler material. This contrasts with the pore size distribution of the materials foamed by other processes where a wider statistical distribution of pores is found. On the other hand, the maximum porosities that can be achieved using space holders are limited to values below 60%, whereas the other methods allow for porosities up to 98%. Temperature of the mould and infiltration pressure are critical process parameters: a typical problem encountered is the premature solidification of the melt, especially due to the high heat capacity of the salt.In this work foam properties such as cell shape, distribution and anisotropy and defect presence are investigated by using digital image processing technique. For this purpose replicated AlSi7Mg0.3 alloy foams are produced by infiltrating preforms of NaCl particles, varying the metal infiltration pressure and the mould preheating temperature.An original procedure based on image analysis has been set up to determine size, morphology and distributionof cells. The paper demonstrates that this methodology, coupled with microstructural analysis, is a useful toolfor investigating the effects of process parameters on foam properties.
Keywords: Replication casting